2008
DOI: 10.1002/casp.980
|View full text |Cite
|
Sign up to set email alerts
|

Pub and community: The views of Birmingham untreated heavy drinkers

Abstract: This paper reports the results of a qualitative analysis of semi-structured interviews with 79 members of the Birmingham Untreated Heavy Drinkers Cohort. The cohort was recruited in 1997 when all participants were drinking 50 or more standard units of alcohol (men) or 35 or more units (women) most weeks. Present interviews were carried out as part of the fourth wave of interviews, held in 2003. The topic was the participants' places of drinking in the community and the functions those places served. The presen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 20 publications
0
15
0
Order By: Relevance
“…The 11 publications were published between 2002 and 2014, and represent six unique studies. The studies took place across England and Scotland, with two unique studies conducted in the North East of England ( Brierley-Jones et al, 2014 ; Wilson et al, 2013 ): one unique study in the West of Scotland ( Emslie, Hunt, & Lyons, 2012 ; Emslie, Hunt, & Lyons, 2013 ; Lyons et al, 2014 ); one study in Blackpool ( Foster & Heyman, 2013 ; Foster et al, 2010 ); one in Birmingham ( Orford et al, 2002 ; Orford et al, 2009 ; Rolfe et al, 2006 ); and one in the South of the UK ( Ritchie, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The 11 publications were published between 2002 and 2014, and represent six unique studies. The studies took place across England and Scotland, with two unique studies conducted in the North East of England ( Brierley-Jones et al, 2014 ; Wilson et al, 2013 ): one unique study in the West of Scotland ( Emslie, Hunt, & Lyons, 2012 ; Emslie, Hunt, & Lyons, 2013 ; Lyons et al, 2014 ); one study in Blackpool ( Foster & Heyman, 2013 ; Foster et al, 2010 ); one in Birmingham ( Orford et al, 2002 ; Orford et al, 2009 ; Rolfe et al, 2006 ); and one in the South of the UK ( Ritchie, 2007 ).…”
Section: Resultsmentioning
confidence: 99%
“…The remaining publications included both men and women of different ages. One paper included participants aged 50 or over ( Wilson et al, 2013 ); three publications from the same study started with a cohort of participants aged 22–50 and followed them over a 10-year period ( Orford et al, 2002 ; Orford et al, 2009 ; Rolfe et al, 2006 ); another paper included participants aged 21–55 ( Brierley-Jones et al, 2014 ); the remaining three publications included a wide range of ages ( Foster & Heyman, 2013 ; Foster et al, 2010 ; Ritchie, 2007 ). Quotes from the papers illustrating their relevance to middle-aged men are presented in S4 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Heavy drinking is another negative attribute mentioned in some of the epitaphs: One more thing I loved very much/To sit at a table in a bar/Next to someone else's wife, and Let me tell you another good one/I enjoyed drinking plum brandy/With my friends at the pub/I often forgot what I came in for . Smokers and heavy drinkers have traditionally been stigmatized within communities and these health threatening behaviours were often related to morality (Farrimond & Joffe, 2006; Orford, Rolfe, Dalton, Painter & Webb, 2009). In the epitaphs these ‘bad habits’ are often mentioned as a violation of moral standards and a subject of social disapproval.…”
Section: Studymentioning
confidence: 99%
“…For example, Wellman (1979Wellman ( ,p.1204 shows how one view bemoans the idea of 'community lost', asserting that industrialisation and urbanisation 6 weaken the sense of solidarity and community among people. Orford et al's (2009) study of pubs in Birmingham (United Kingdom), drawing from this concept, also found that some pub users felt that a decline in pubs was contributing to just such a loss of community. Although focussing on community in urban settings, their analysis is also relevant to village life where community is often seen as threatened by such phenomena as closing pubs or growing numbers of rural second homes, given the common assumption that 'users of second homes lack any connection with "host" communities' (Gallent, 2007,p.99).…”
Section: The Nature Of Communitymentioning
confidence: 99%